Fading Spectrophotometric Determination of Cefoperazone Sodium in Injections by Fe3+-Sulfosalicylic Acid System - Chen, Li; Sha, Ou; Zhai, Wen-Ji; Yang, Jing-Hua (Asian Journal of Chemistry, 2013)
A new fading spectrophotometric methods was founded for the determination of cefoperazone sodium. In the acid medium, sulfosalicylic acid could react with Fe3+ to form a complex which has the maximum absorbance at 510 nm. Fe(III) could be reduced to Fe(II) by sulfydryl which is the degradation product of cefoperazone sodium under heat condition. So the absorbance of binary complex Fe(III)-sulfosalicylic acid in the solution could be decreased by a decrease in the concentration of Fe(III) for the redox reaction between Fe(III) with sulfydryl. It was found that the concentration of cefoperazone sodium has a good linear with the absorbance. The parameter of the experiment was investigated and optimized. Under the optimum conditions, the absorbance and the concentration of ceftriaxone sodium was linear in the range of 0.50-12.5 mg/L. The regression equation was A = 0.04808c (mg/L) + 0.523, the average recovery rate of samples in the system was 98.8-101.4 %. The proposed methods have been applied to the determination of cefoperazone sodium content in injections with satisfactory results.